Oral Communication Skills of the Students of Osias Colleges, Inc. - Salagan, Aurea C. (Future Science / FSH-PH Publications, 2024)
The study employed a descriptive design to gather baseline data on respondents' oral communication skills in English. The results revealed that the majority of respondents were female, aged 19-24, who primarily spoke Tagalog and Ilokano at home, and were mainly in their second and third years of study. Utilizing a 5-point Likert scale for assessment, the findings indicated that respondents were rated as